2004
DOI: 10.1021/ac049255b
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Tissue Analysis of Neuropeptides by MALDI FTMS In-Cell Accumulation

Abstract: Herein we report the first application of Fourier transform mass spectrometry for the analysis of neuropeptides directly from neuronal tissues. Sample preparation protocols and instrumentation conditions are developed to allow in situ neuropeptide analysis of the neuroendocrine organs freshly isolated from a marine organism Cancer borealis. The utility of a previously developed in-cell accumulation (ICA) technique is extended for peptide analysis in complex tissue samples. With the ICA procedure, ion signals f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
126
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 89 publications
(129 citation statements)
references
References 59 publications
2
126
1
Order By: Relevance
“…Recent studies showed that the application of MALDI-FTMS holds significant advantages over other types of mass spectrometry (21,22). FTMS provides very high mass accuracy, which is considerably increased by its ability to perform an internal calibration (23).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that the application of MALDI-FTMS holds significant advantages over other types of mass spectrometry (21,22). FTMS provides very high mass accuracy, which is considerably increased by its ability to perform an internal calibration (23).…”
Section: Discussionmentioning
confidence: 99%
“…Desalted extracts were mixed 1:1 with DHB matrix (150·mg·ml -1 in 50% methanol/deionized water) on a MALDI probe tip and allowed to crystallize at room temperature. MALDI-FTMS analysis was then performed as described in several recent publications (Kutz et al, 2004;Messinger et al, 2005) using an IonSpec HiResMALDI Fourier transform mass spectrometer equipped with a 7.0-T actively shielded superconducting magnet (School of Pharmacy, University of Wisconsin-Madison).…”
Section: Maldi-ftms Of Hemolymph Extractsmentioning
confidence: 99%
“…By using MALDI-FTICR (Fourier transform ion cyclotron resonance) MS it is possible to combine high resolving power, high mass accuracy, and the possibility of performing multistage MS/MS experiments [35][36][37][38] allows peptide identification directly from tissue [39].°The°FTICR°imaging°strategy°extends°the°identifi-cation possibilities in direct tissue analysis and is a valuable tool in MS imaging instrumentation.…”
mentioning
confidence: 99%